2001
DOI: 10.1046/j.1525-1446.2001.00178.x
|View full text |Cite
|
Sign up to set email alerts
|

The Art of Motivating Behavior Change: The Use of Motivational Interviewing to Promote Health

Abstract: Health promotion and disease prevention have always been essential to public health nursing. With the changing health care system and an increased emphasis on cost-containment, the role of the nurse is expanding even more into this arena. A challenge for public health nurses, then, is to motivate and facilitate health behavior change in working with individuals, families, and communities and designing programs based on theory. Leading causes of death continue to relate to health behaviors that require change. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 24 publications
0
65
0
Order By: Relevance
“…increasing health-related knowledge, which might increase control over health-related factors. An interesting development within healthcare, traditionally very behavior-change oriented, is the move towards more participatory strategies, such as 'motivational interviewing' (Miller and Rollnick, 2002), used, for example, to achieve smoking cessation (Schinitzky and Kub, 2001).…”
Section: Autonomy and Control As Predetermined Goalsmentioning
confidence: 99%
“…increasing health-related knowledge, which might increase control over health-related factors. An interesting development within healthcare, traditionally very behavior-change oriented, is the move towards more participatory strategies, such as 'motivational interviewing' (Miller and Rollnick, 2002), used, for example, to achieve smoking cessation (Schinitzky and Kub, 2001).…”
Section: Autonomy and Control As Predetermined Goalsmentioning
confidence: 99%
“…From a review of 23 such studies, none of which was from the UK (21 from the USA, one in Australia and one in France), we concluded that there was limited evidence for the effectiveness of healthy eating interventions in the elderly. 147 However, the review did find that the strategies of individual feedback and goal-setting highlighted previously 142 were beneficial and were associated with a positive intervention. 147 The review restated the fact that the elderly community dwelling population is a heterogeneous group and that more research is required to identify suitable approaches at different age groups, social class and health status.…”
Section: Interventions For Elderly People Living In the Communitymentioning
confidence: 95%
“…Motivational interviewing can be used in the model to assess in what stage a patient is and different stage-directed strategies can then be used (Compton et al, 1999;Shinitzky & Kub, 2001). …”
Section: Stages Of Change (Soc) Modelmentioning
confidence: 99%
“…The education, which also contained training on how to use the SOC model, contributed to the structure of the consultations. The usefulness of having the SOC model as a framework in health-promotion is pointed out in a review of promoting evidencebased practice (Crookes et al, 1997) and in a review of motivating behavioural change (Shinitzky & Kub, 2001). As a result of the education, the nurses also had their knowledge of hypertension and its treatment updated, which gives confidence in the treatment of patients and the opportunity to popularise the topic in question (Weir et al, 2000).…”
Section: Non-pharmacological Treatmentmentioning
confidence: 99%